(untitled) (Caligrama: Revista de Estudos Românicos, 2020)
Resumo: O artigo se dedica a recortar trechos da peça Οἰδίπους τύρρανος, de Sófocles, aqui traduzida como Édipo zorro, e traduzi-los. O leitmotiv que dirige a seleção é o enfrentamento de Édipo, é de difícil tradução. Sófocles explora a potência dos sentidos lexicais e sintáticos da língua grega ao máximo, a começar pelo título que chegou até nós para a peça – que daria um tratado – se o focalizarmos apenas com o adjetivo (que não é adjetivo, mas substantivo utilizado como adjetivo) τύρρανος. A tradução Édipo Rei é neutralizante; a tradução Édipo Tirano é tendenciosa, capciosa e política demais para um termo que poderia ser traduzido de outras formas, entre as quais a que escolhemos. Por sua vez, o nome próprio Édipo, etimologicamente, suscita variações incríveis e pertinentes se optamos por traduzi-lo. O artigo não pretende discutir filologia nem literatura a fundo, vamos apenas, com uma proposta de tradução, mostrar a pertinência do Édipo para o Brasil em pandemia. Palavras-chave: tragédia; governança; responsabilidade; peste; tradução. Abstract: The article aims at selecting excerpts from Sophocles’ play Oedipus Tyrannus, starred here as Oedipus the fox, and translating them. The leitmotiv that directs the selection is the confrontation of the plague by the ruler. As it is well known, the Sophoclean text, and particularly that which refers to the drama of Oedipus, is difficult to translate. Sophocles uses the power of the lexical and syntactic meanings of the Greek language to the maximum, starting with the title that came to us for the play - which would give a treatise - if we focus on it only with the adjective (which is not an adjective, but a noun used as an adjective) τύρρανος. The Oedipus king translation is neutralizing; the Oedipus tyrant translation is too biased, too captious, and too political for a term that could be translated in other ways such as the one we chose. In turn, the word Oedipus, etymologically, gives rise to incredible and pertinent variations if we choose to translate it. The article does not intend to discuss philology nor literature in depth, I will just go with a translation proposal to show the relevance of Oedipus for Brazil in a pandemic. Keywords: tragedy; governance; responsibility; plague; translation.